War as an Accession Accelerator? Ukraine’s Path Towards the EU - Mazur, Sylwia Katarzyna (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The European Union’s response to the war in Ukraine is perceived as swift and relatively coherent. The political willingness to support its attacked neighbour has also extended to Ukraine’s membership bid. Despite protracting war and worsening Ukraine’s position, there are no doubts over the state’s commitment to reforms. For now, it can be safely assumed that Ukraine will pursue its path towards membership. Can fighting war and pushing an arduous accession process be balanced by the political will of the EU Member States rooted in a wartime gesture of solidarity?